Annual banned‐substance review: analytical approaches in human sports drug testing. Issue 1 (10th December 2012) - Thevis, Mario; Kuuranne, Tiia; Geyer, Hans; Schänzer, Wilhelm; Kerwin, Jim
<x xml:space="preserve">Abstract</x> Frequently updated anti‐doping regulations and detection strategies for banned substances and methods of doping are vital for efficient and scientifically substantiated abatement of drug abuse, manipulation, and illicit performance enhancement in sport. In 2012, the ninth version of the Prohibited List as annually issued by the World Anti‐Doping Agency (WADA) reports on modest but relevant modifications from its 2011 predecessor. Awareness of old and new analytical challenges in sports drug testing, together with issues resulting from altered rules and regulations, have given rise to numerous research projects aiming at improved detection strategies to strengthen international anti‐doping efforts. In this annual banned substance review, emerging and advancing methods in the detection of known and recently outlawed substances are reported. New and/or enhanced procedures and techniques of doping analysis are reviewed together with information relevant to doping controls. The review surveys and critiques literature published between October 2011 and September 2012. Copyright © 2012 John Wiley & Sons, Ltd.